2012
DOI: 10.1159/000338919
|View full text |Cite
|
Sign up to set email alerts
|

Poor Compliance with Guidelines on Anemia Treatment in a Cohort of Chronic Hemodialysis Patients

Abstract: Background/Aims: Guidelines for the management of anemia and iron deficiency in chronic hemodialysis (HD) patients have been developed to standardize therapy and improve clinical outcome. The present study evaluated compliance with anemia guidelines and investigated whether differences between centers were present. Methods: Data on anemia management from patients in the baseline cohort of the CONTRAST study (NCT00205556) were analyzed. 598 chronic HD patients (62% male, age 63.6 ± 14.0 years) from 26 Dutch dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Guidelines for the management of anemia and iron deficiency in chronic hemodialysis (HD) patients have been developed to standardize therapy and improve clinical outcome. But a recent Dutch study found that compliance with anemia targets in stable HD patients was poor and showed a wide variation between treatment facilities [40].…”
Section: Anemiamentioning
confidence: 99%
“…Guidelines for the management of anemia and iron deficiency in chronic hemodialysis (HD) patients have been developed to standardize therapy and improve clinical outcome. But a recent Dutch study found that compliance with anemia targets in stable HD patients was poor and showed a wide variation between treatment facilities [40].…”
Section: Anemiamentioning
confidence: 99%
“…This study demonstrated that the compliance with all anemia targets (Hb 11.0-12.0 g/dl, transferrin saturation ratio ≥20%, ferritin 100-500 ng/ml) was reached in only 12% of the patients. The adherence percentages varied greatly among centers (4-26%), even after adjustment for treatment-related factors and center-specific characteristics [22]. …”
Section: Other Findings In the Contrast Populationmentioning
confidence: 99%
“…The World Health Organization (WHO) defines anemia as hemoglobin level less than 13 g/dl in men and less than 12 g/dl in women (6). In the hemodialysis patients, the hemoglobin levels over 13 g/dl are not associated with a decrease in cardiovascular disease and their mortality rates, and their recommended hemoglobin levels are over 11 g/dl (8).…”
Section: Introductionmentioning
confidence: 99%